Penerapan Model Pembelajaran Window Shopping Terhadap Hasil Belajar IPA Siswa Kelas V UPTD SDN 97 Inpres Tellumpanuae Kabupaten Maros - Nur Hidayah Bahrun; Nurlina Nurlina; Rahmatia Tahir (Lembag, 2024)
The aim of this research is to determine the application of the Window Shopping Learning Model to the Science Learning Outcomes of Class V UPTD SDN 97 Inpres Tellumpanuae Students, Maros Regency. This research is a type of pre-experimental research with a research design using a one group Pretest-Posttest design using a quantitative approach. This design carries out two measurements, first (Pretest) and second measurement (Posttest). The sample in this research was class V UPTD SDN 97 Inpres Tellumpanuae, totaling 23 students. The results of the research showed that the average student pretest result was 53.70 in the low category, then the window shopping learning model was applied to the learning process so that the students' posttest results reached a value The average is 79.35 in the medium category. N-Gain analysis shows the gain is 65.41 in the medium category.